Readings from programming with Python - McMullen, Kyla; Elizabeth Matthews, June Jamrich Parsons (Boston : Cengage, 2023)
Ideal for beginners, this book helps students develop a useful understanding of computer science while equipping them with the skills to use Python programming language
Keywords: Computer Engineering